If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 20 = 8x + 4 Reorder the terms: 20 + 6x = 8x + 4 Reorder the terms: 20 + 6x = 4 + 8x Solving 20 + 6x = 4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 20 + 6x + -8x = 4 + 8x + -8x Combine like terms: 6x + -8x = -2x 20 + -2x = 4 + 8x + -8x Combine like terms: 8x + -8x = 0 20 + -2x = 4 + 0 20 + -2x = 4 Add '-20' to each side of the equation. 20 + -20 + -2x = 4 + -20 Combine like terms: 20 + -20 = 0 0 + -2x = 4 + -20 -2x = 4 + -20 Combine like terms: 4 + -20 = -16 -2x = -16 Divide each side by '-2'. x = 8 Simplifying x = 8
| -2.7x^2+35x+3=0 | | 3x+33y=-24 | | 5x+19=8x+7 | | 9+16/4+5*6 | | 19+5-8*4/2 | | 9/10+y/7 | | 9/10+y/1 | | 24/12+5*7 | | -25/8*64/9 | | b/a=15 | | -4(-4v-u)-5(-6u+3v)= | | -31/8*71/9 | | 3t-10=-20/t | | yz=20 | | 147v^2-192= | | 3t-10=-20+t | | y=z+15 | | 21/3*6 | | d/3+1/3=4d-1/12 | | y=-10/9+10 | | 8x-28=-22+2x | | 20=z+y | | (6+8)^2/7 | | 2400/36 | | 5y+2(y-6)=3(y+2)-3 | | 9(y-1)/4=-3y | | 10-2t=2 | | 4d^2+32d+64= | | 5(2x-8)-2=10x-42 | | (-3-7)/(6-2) | | ax-28=-22+2x | | 8x+7=8(x-8) |